Model Pendampingan Ikatan Kerukunan Pemuda Paccinongang (IKPP) Terhadap Remaja Broken Home di Kelurahan Paccinongang Kabupaten Gowa - Irawati Ali (Jurnal Berita Sosial, 2023)
This research is a qualitative study using sociological research methods, while the research location is located in Paccinongang Village, Gowa Regency, the data source of this research is secondary data sources and primary data sources. Data collection methods were observation, interview and documentation. Research instruments used cameras, notebooks, stationery, recording devices, cellphones, and interview guidelines. After all was summarized, the researcher analyzed the data by reducing the data (data reduction). Presentation of data (data display), and drawing conclusions. The results of this study indicate that the assistance model of the Paccinongang Youth Harmony Association in assisting broken home adolescents in Paccinongang Village; 1) The Paccinongang Youth Harmony Association’s assistance model for broken home adolescents is a social action model by directly embracing adolescents and providing motivation as familiarity begins to blend in so that adolescents are easier to realize their vision, mission and goals. 2). Factors causing broken homes in Paccinongang Village such as: (a) The factor of divorced parents, (b) Economic factors, (c) Busyness factors / lack of affection from parents